2008
DOI: 10.1002/adma.200702411
|View full text |Cite
|
Sign up to set email alerts
|

Grinding a Nanotube

Abstract: Field evaporation phenomena, the removal of atoms from positively charged surfaces at strong field of tens of volts per nanometer, are of tremendous scientific and technological importance. The technique of field-ion microscopy (FIM) has been developed based on this phenomenon, and is historically the first technique to have achieved atomic resolution. [1,2] The atom probe, a variation of FIM, came later and is generally used to identify the species of atoms that are being individually evaporated from the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 32 publications
(30 reference statements)
0
35
0
Order By: Relevance
“…21,22 As suggested in previous studies, the end of a CNT subjected to an electrical field of a few tens V nm −1 could undergo a structural evolution via positive field evaporation. 23 Meanwhile, the contaminants at the CNT apex can also be removed efficiently by this method (See Figure S2). 24 After this treatment, the resulting CNT tip usually exhibited consistent performance in the following experiment of imaging and work function measurements (See Supporting Information for details).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21,22 As suggested in previous studies, the end of a CNT subjected to an electrical field of a few tens V nm −1 could undergo a structural evolution via positive field evaporation. 23 Meanwhile, the contaminants at the CNT apex can also be removed efficiently by this method (See Figure S2). 24 After this treatment, the resulting CNT tip usually exhibited consistent performance in the following experiment of imaging and work function measurements (See Supporting Information for details).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The possibility of using the fi eld emission process to controllably modify the freestanding tip of a CNT was again picked up in 2008 [ 71 ]. Previously, sharpening of the CNT had been reported but this required direct contact of the tip to another CNT [ 63 ].…”
Section: Carbon Nanotubesmentioning
confidence: 98%
“…Sveningsson et al [5] measured the electron emission from carbon nanotubes and observed that for low currents the emission was of a standard Fowler-Nordheim type, while for higher emission currents a nonlinear behavior occurred due to thermally enhanced emission caused by Joule heating of the carbon nanotube. A detailed study of the correlation of the structure of carbon nanotubes and electron emission as well as the structural change during emission was done by Wang et al [55]. An interesting combination of the resonance method to determine the work function [56,57] and field emission was done by Xu et al [58].…”
Section: Field Emissionmentioning
confidence: 98%